2018
DOI: 10.1371/journal.pone.0207947
|View full text |Cite
|
Sign up to set email alerts
|

Metformin induces significant reduction of body weight, total cholesterol and LDL levels in the elderly – A meta-analysis

Abstract: BackgroundMetformin is the first-choice drug for patients with Type 2 diabetes, and this therapy is characterized by being weight neutral. However, in the elderly an additional unintentional weight loss could be considered as an adverse effect of the treatment.ObjectivesWe aimed to perform a meta-analysis of placebo-controlled studies investigating the body weight changes upon metformin treatment in participants older than 60 years.Materials and methodsPubMed, EMBASE and the Cochrane Library were searched. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 40 publications
5
50
0
2
Order By: Relevance
“…Studies suggest that metformin treatment of obese adults with type 2 diabetes could lead to weight loss and improved glucose tolerance as well as fat reserves. Metformin mainly exerts its anti-hyperglycemic effect by reducing the excretion of hepatic glucose through inhibiting gluconeogenesis causing reduced weight and blood glucose in type 2 diabetic patients [31]. Metformin appears to be effective in blood glucose control, lipid status, and weight control and can be a good therapy in obese type 2 diabetic patients.…”
Section: Bwimentioning
confidence: 99%
“…Studies suggest that metformin treatment of obese adults with type 2 diabetes could lead to weight loss and improved glucose tolerance as well as fat reserves. Metformin mainly exerts its anti-hyperglycemic effect by reducing the excretion of hepatic glucose through inhibiting gluconeogenesis causing reduced weight and blood glucose in type 2 diabetic patients [31]. Metformin appears to be effective in blood glucose control, lipid status, and weight control and can be a good therapy in obese type 2 diabetic patients.…”
Section: Bwimentioning
confidence: 99%
“…In another study done in adult obese women without resistance to insulin, who were given 500 mg of MTF twice a day for three months, no differences were found in body weight, body fat, and blood pressure levels, neither did the glucose, insulin, and IGF-1 plasma levels decreased [48]. A recent meta-analysis [49] showed that MTF treatment in elderly humans moderately diminishes body weight, along with a significant decrease in serum cholesterol and LDL, which could suggest a reduction in the risk of major coronary events and of mortality in elderly diabetic populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lowering blood glucose, metformin consistently induces weight loss in people with or without type 2 diabetes [16][17][18][19][20][21] . This effect on weight loss is not due to increases in energy expenditure 17,22 , but instead involves the suppression of appetite 18,23 .…”
mentioning
confidence: 99%